A Review of Problems Facing Science Education in Basic Education in Nigeria and Way Forward - Aibe Joseph Ndayebom; Ogunode, N, J. (Researchparks Publishing, 2022)
Science education at the basic education is key to the development of science education in the future. The foundation of science education matters a lot in the development of science programme. Science education at the basic education in Nigeria is plagued with many problems. This paper intends to discuss the problems militating against effective teaching and learning of science education at the basic schools in Nigeria. Primary and Secondary data were used to provide empirical support for the points raised in the paper. The secondary data were sourced from print materials and online resources. The paper concluded that inadequate funding, shortage of science teachers, shortage of infrastructural facilities, corruption, lack of instructional materials and poor capacity building and insecurity problems were identified the problems militating against effective teaching and learning of science education at the basic schools in Nigeria. To address this problems, the paper among other things, recommended that the government at every level should increase the funding of science programme in the primary school education in Nigeria. This will help to provide all the materials and human resources needed for the implementation of the programme at the school level.